The Application of Visual Media in Developing Response And Suggestion Writing Skills in Elementary School-Age Children - Rambe, Riris Nurkholidah; Nadhifah, Dinah; Juliani, Siti Fifi; Azhari, Wahyu; Siregar, Nepri Handayani; Janani, Khairina (Yayasan Pendidikan Islam Akmalia, 2023)
Writing skills are a way for someone to describe ideas, ideas, thoughts in written form that can be read and understood by readers. This paper aims to determine the application of visual media in developing students' skills in writing responses and suggestions, as well as the supporting and inhibiting factors of the visual media. This research was conducted using a descriptive qualitative approach to describe a research result, provide a description, explanation, as well as validation regarding the phenomenon being studied by observation or observation, interviews, and documentation. Based on this research it was found that the application of visual media in writing skills has an impact, namely, (1) students can understand learning material with visual media in the form of images, (2) students can answer questions by writing sentences and suggestions based on the pictures contained in the problem, and (3) all students write down the answers correctly and get good grades. (4) Students dare to read their writing in front of all their friends. Then the supporting factor is the teacher's proficiency in using the media, and also visual learning media has the benefit of being able to introduce original pictures of an object or event. While the inhibiting factors in the use of visual learning media are limited facilities and lack of funds for adequate learning media facilities